IMPROVING LEARNING OUTCOMES IN WRITING POETRY THROUGH CONTEXTUAL TEACHING LEARNING (CTL) IN CLASS V STUDENTS - Reni Dangon; Sundari Hamid; Asdar Asdar (Teaching English as a Foreign Language Overseas Journal, 2022)
The purpose of this study was to determine whether the learning outcomes of Indonesian language poetry writing materials for fifth grade students could be increased through the application of the contextual teaching and learning (C This research is classroom action research (CAR). The results showed an increase in student learning outcomes. In the first cycle, the average score reached 71 with a learning completeness percentage of 68%. In the second cycle, the average value reached 79.25, an increase of 8. 25 points from cycle I with a percentage of learning completeness of 92%. Based on the data on learning outcomes in cycle I and cycle II, it can be concluded that learning has been considered successful because cycle II has met the learning mastery criteria of 75%. From the results obtained, it can be concluded that the use the Contextual Teaching and Learning (CTL) approach can improve student learning outcomes.